How The Role of Electronic Human Resource System (E-System), Environment, Job Satisfaction on Employee Performance? An Empirical Study on Private Bank Employee - Muhammad Ramdhan (Universitas Dharma Wacana, 2022)
The purpose of this study is to analyze the relationship between the work environment on job satisfaction, the relationship between the HR e-system on job satisfaction, the relationship between the work environment and employee performance, the relationship between the HR e-system on employee performance, the relationship between job satisfaction and employee performance. This study uses a quantitative approach. The scope of the research object is determined by the variables of the HR e-System, Work Environment, Job Satisfaction, Work Motivation, and Bank Employee Performance. The sampling technique uses purposive sampling. The number of samples specified in this study were 500 respondents who were distributed through Google Form. Data collection techniques can be done with online questionnaires distributed through social media. Sources of data that directly provide data to data collectors are derived from primary sources by distributing tools, namely questionnaires to employees at the Bank. The instrument uses a questionnaire with a Likert scale using 5 (five) scores ranging from answers to statements provided through tools from a scale of '1' Strongly Disagree to a scale of '5' Strongly Agree. Data analysis techniques use structural equation modeling (structural equation modeling). or abbreviated as SEM. This research data processing tool uses the SmartPLS application or software. The results of this study are that there is a positive and significant relationship between the work environment and job satisfaction. There is a positive and significant relationship between the HR e-system on job satisfaction. There is a positive and significant relationship between the work environment and employee performance. There is a positive and significant relationship between the HR e-system on employee performance. There is a positive and significant relationship between job satisfaction and employee performance